Pharmacoeconomic evaluation of anti-obesity drugs for chronic weight management: a systematic review of literature - Xue, Yan; Zou, Huimin; Ruan, Zhen; Chen, Xianwen; Lai, Yunfeng; Yao, Dongning; Ung, Carolina Oi Lam; Hu, Hao (Frontiers in Endocrinology, 2023)
Introduction: Pharmacological therapy is recommended as a second-line alternative to reverse obesity. Currently, five anti-obesity drugs (AODs) have been approved by the U.S. Food and Drug Administration (FDA) for chronic weight management. The aim of this paper is to investigate the pharmacoeconomic evaluation of AODs through a systematic review with a special focus on methodological considerations. Methods: We searched the general and specific databases to identify the primary pharmacoeconomic evaluation of AODs.Results: A total of 18 full-text articles and three conference abstracts were included in this review. Most of the economic assessments were still about Orlistat. And the observations we could make were consistent with the previous systematic review. A few studies were on the combined therapies (i.e. PHEN/TPM ER and NB ER) compared to different comparators, which could hardly lead to a generalized summary of the cost-effectiveness. Most recently, pharmacoeconomic evidence on the newest GLP 1 RA approved for the indication of obesity or obesity with at least one comorbidityemerged gradually. Modelling-based cost-utility analysis is the major type of assessment method. In the modelling studies, a manageable number of the key health states and the state transitions were structured to capture the disease progression. In particular, the principal structure of 2 This is a provisional file, not the final typeset article the decision model adopted in the three studies on the newly approved drug was nearly the same, which enables more in-depth comparisons and generalisations of the findings.Conclusions: This study provided an up-to-date overview of the strengths and areas for improvement in the methodological design of the pharmacoeconomic evaluation of the licensed drugs for chronic weight management. Future modelling evaluations would benefit from a better understanding of the long-term weight loss effects of the current therapeutic options and the weight rebound process after the discontinuation of treatment.